Screening papaveraceae as novel antibiofilm natural‐based agents - Sylwia Zielińska; Magdalena Dziągwa‐becker; Adam Junka; Ewelina Piątczak; Anna Jezierska‐domaradzka; Malwina Brożyna; Justyna Paleczny; Aleksandra Sobiecka; Wojciech Słupski; Eleonora Mess; Mariusz Kucharski; Serhat Sezai Çiçek; et al. (Molecules, 2021)
The antimicrobial properties of herbs from Papaveraceae have been used in medicine for centuries. Nevertheless, mutual relationships between the individual bioactive substances contained in these plants remain poorly elucidated. In this work, phytochemical composition of extracts from the aerial and underground parts of five Papaveraceae species (Chelidonium majus L., Corydalis cava (L.) Schweigg. and Körte, C. cheilanthifolia Hemsl., C. pumila (Host) Rchb., and Fumaria vaillantii Loisel.) were examined using LC‐ESI‐MS/MS with a triple quadrupole analyzer. Large differences in the quality and quantity of all analyzed compounds were observed between species of different genera and also within one genus. Two groups of metabolites predominated in the phytochemical profiles. These were isoquinoline alkaloids and, in smaller amounts, non‐phenolic carboxylic acids and phenolic compounds. In aerial and underground parts, 22 and 20 compounds were detected, respectively. These included: seven isoquinoline al-kaloids: protopine, allocryptopine, coptisine, berberine, chelidonine, sanguinarine, and chelerythrine; five of their derivatives as well as non‐alkaloids: malic acid, trans‐aconitic acid, quinic acid, salicylic acid, trans‐caffeic acid, p‐coumaric acid, chlorogenic acid, quercetin, and kaempferol; and vanillin. The aerial parts were much richer in phenolic compounds regardless of the plant species. Characterized extracts were studied for their antimicrobial potential against planktonic and biofilm‐producing cells of S. aureus, P. aeruginosa, and C. albicans. The impact of the extracts on cellular metabolic activity and biofilm biomass production was evaluated. Moreover, the antimicrobial activity of the extracts introduced to the polymeric carrier made of bacterial cellulose was assessed. Extracts of C. cheilanthifolia were found to be the most effective against all tested human pathogens. Multiple regression tests indicated a high antimicrobial impact of quercetin in extracts of aerial parts against planktonic cells of S. aureus, P. aeruginosa, and C. albicans, and no direct correlation between the composition of other bioactive substances and the results of antimicrobial activity were found. Conclusively, further investigations are required to identify the relations between recognized and unrecognized compounds within extracts and their biological properties.
Keywords: Berberine; Chelerythrine; Chelidonium majus; Chlorogenic acid; Coptisine; Corydalis cava; Corydalis cheilanthifolia; Corydalis pumila; Fumaria vail-lantii; Protopine; Quercetin